ضغوط العمل للمرأة العاملة وأثرها على الرضا الوظيفي دراسة حالة مركز البحث العلمي والتقني حول المناطق الجافة عمر البرناوي (C.R.S.T.R.A)– بسكرة – الجزائر (المجلة العراقية للعلوم الاقتصادية, 2018)
This study aims to identify the sources of stress at work experienced by women working in the center of scientific and technical research on arid and semi-arid areas (Omar Bernaoui), also aims to introduce the glass ceiling phenomenon and highlight their causes, and to study the possibility of this exposureofwemen working at the center of scientific research, to it and more that we want to know whether workers have been subjected to discrimination in the field of promotion and training. in these circumstances, we seek to determine the level of job satisfaction among women workers at the center of scientific research. We have adopted in our study the process of the case study with the descriptive approach and research applied the tools to 56 women who work in the center of scientific research, and the responses were submitted to necessary statistical processing.